Perancangan dam Pembuatan Media Pembelajaran Ilmu Pengetahuan Alam (IPA) Berbasis Augmented Reality Kelas IX SMP Negeri 2 Pancung Soal - Ovan.S. Efendi; Indra Wijaya; Popi Radyuli (Culture education and technology research (Cetera), 2024)
This research aims to produce and determine the level of validity, practicality and effectiveness of Natural science learning media (IPA) using augmented reality class IX SMP Negeri 2 Pancung Soal. This research uses the R&D (research & development) research development method. The research subjects were 55 people. The development model used is the ADDIE model, with the design of the development steps being as follows. (1) Analyze, (2) design, (3) development, (4) Implementation and (5) Evaluate. The results of the validity test by the experts as a whole the validator test assessment of Natural science learning media (IPA) using augmented reality class IX SMP Negeri 2 Pancung Soal was 90,72%, with a very valid interpretation used. The results of the practicality test assessment as a whole the practicality assessment of Natural science learning media (IPA) using augmented reality class IX SMP Negeri 2 Pancung Soal was 97,02%, with a very practical interpretation to use. The results of the evaluation test for the overall effectiveness Natural science learning media (IPA) using augmented reality class IX SMP Negeri 2 Pancung Soal were 94%, with very effective interpretations used. In conclusion, that the natural science (IPA) learning media using augmented reality as a learning media has been tested for its suitability, excellence, and can be used in the learning process in the natural science (IPA) subject in class IX of SMP Negeri 2 Pancung Soal.